The Use of Advanced Environmentally-friendly Systems in the Insulation and Reconstruction of Buildings - Zach, Jiří; Novák, Vítězslav; Peterková, Jitka; Bubeník, Jan; Košir, Mitja; Božiček, David; Krejza, Zdeněk (MDPI, 2023)
This study is devoted to the possibility of using advanced insulation materials, such as Vacuum Insulation Panels (VIP), in the insulation and reconstruction of buildings, in connection with the green elements that are installed on the facade in the case of the use of external thermal insulation composite systems (ETICS). The use of VIP as part of the insulation system will result in a significant reduction in the required thickness of the insulation layer. In turn, the reduced overall thickness of the system will allow for easier direct anchoring of the elements of the green facade through the insulating layer to the base of the structure. The research carried out proves that, by using VIP in the insulation system (with a VIP thickness of 30 mm in combination with 20 mm of extruded polystyrene XPS), the thermal insulation properties can be significantly improved and, thus, the thickness of the insulation system can be reduced to 1/3 of the thickness of conventional insulation (while achieving the same thermal resistance), thereby enabling the anchoring of green elements on the surface of such an insulation system.

This study is devoted to the possibility of using advanced insulation materials, such as Vacuum Insulation Panels (VIP), in the insulation and reconstruction of buildings, in connection with the green elements that are installed on the facade in the case of the use of external thermal insulation composite systems (ETICS). The use of VIP as part of the insulation system will result in a significant reduction in the required thickness of the insulation layer. In turn, the reduced overall thickness of the system will allow for easier direct anchoring of the elements of the green facade through the insulating layer to the base of the structure. The research carried out proves that, by using VIP in the insulation system (with a VIP thickness of 30 mm in combination with 20 mm of extruded polystyrene XPS), the thermal insulation properties can be significantly improved and, thus, the thickness of the insulation system can be reduced to 1/3 of the thickness of conventional insulation (while achieving the same thermal resistance), thereby enabling the anchoring of green elements on the surface of such an insulation system.
The Use of Advanced Environmentally-friendly Systems in the Insulation and Reconstruction of Buildings
Keywords: Insulation materials; vacuum insulation panels; environmentally-friendly system; Insulation materials; vacuum insulation panels; environmentally-friendly system